(untitled) (Research, Society and Development, 2020)
Objective: To investigate the influence of the caregiver on the organization and functioning of the Home Care Service in the modalities AD2 and AD3. Methodology: Descriptive, exploratory study with qualitative approach, carried out with the two coordinators of the Home Care Service in modalities 2 and 3 in the city of Porto Alegre. Data collection occurred through semi-structured interviews from September 2018 to October 2019 and for data analysis we opted for bardin content analysis. Results: Caregivers are essential considering that their presence is necessary as one of the criteria for the user’s admission to the service or in some cases the exclusion of the same when the therapeutic plan or routines assigned by the service team are not performed. Conclusion: The presence of the caregiver is capable of influencing the eligibility and exclusion of the user in the SAD in the modalities AD2 and AD3, as well as in the activities developed in this service, because it is considered a fundamental element for continuity of care at home, besides acting as a link between the patient and the team.